Pengaruh Produk Domestik Regional Bruto, Pajak Daerah, dan Jumlah Penduduk terhadap Pendapatan Asli Daerah Jawa Tengah Tahun 2021-2023 - Oktiva Putri Ariana; Sri Laksmi Pardanawati; Rukmini Rukmini (Jurnal Pajak dan Analisis Ekonomi Syariah, 2026)
This study aims to analyze the effect of Gross Regional Domestic Product (GRDP), Local Taxes, and Population on Local Own-Source Revenue (PAD) in 35 regencies/cities of Central Java Province during 2021–2023. The study employs a quantitative approach using secondary data obtained from the Central Java Statistics Agency (BPS) and Local Government Budget Realization Reports (LRA). The sample was selected using a census sampling technique and analyzed using multiple linear regression after classical assumption testing. The results indicate that GRDP and Local Taxes have a significant effect on PAD, while Population does not have a significant effect on PAD. These findings imply that local governments should prioritize regional economic growth and optimize local tax collection to strengthen fiscal capacity rather than relying solely on population growth. The novelty of this study lies in its integrated examination of GRDP, Local Taxes, and Population across all 35 regencies/cities in Central Java during the 2021–2023 period, providing updated empirical evidence to support regional fiscal policy and local revenue optimization.